2022
DOI: 10.1001/jamasurg.2021.5856
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Pulmonary Vasodilator Therapy in Adult Lung Transplant

Abstract: IMPORTANCE Inhaled nitric oxide (iNO) is commonly administered for selectively inhaled pulmonary vasodilation and prevention of oxidative injury after lung transplant (LT). Inhaled epoprostenol (iEPO) has been introduced worldwide as a cost-saving alternative to iNO without high-grade evidence for this indication.OBJECTIVE To investigate whether the use of iEPO will lead to similar rates of severe/grade 3 primary graft dysfunction (PGD-3) after adult LT when compared with use of iNO.DESIGN, SETTING, AND PARTIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Inhaled NO can improve oxygenation by reducing the alveolar shunt volume and shows a pronounced reduction in right ventricular afterload without affecting systemic afterload [ 73 ]. Studies on the effects during transplantation demonstrated an improvement in oxygenation and a decrease in pulmonary arterial pressure [ 74 ]. However, randomised clinical data demonstrating an improvement in outcome are lacking.…”
Section: Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Inhaled NO can improve oxygenation by reducing the alveolar shunt volume and shows a pronounced reduction in right ventricular afterload without affecting systemic afterload [ 73 ]. Studies on the effects during transplantation demonstrated an improvement in oxygenation and a decrease in pulmonary arterial pressure [ 74 ]. However, randomised clinical data demonstrating an improvement in outcome are lacking.…”
Section: Strategymentioning
confidence: 99%
“…A more recent study compared iNO with inhaled epoprostenol, which is significantly less expensive. There were no differences in outcome [ 74 ]. Side effects of iNO include renal failure, methaemoglobinaemia, and in the experimental setting, platelet dysfunction.…”
Section: Strategymentioning
confidence: 99%
“…Therefore, the routine use of inhaled NO in lung transplantation is not recommended, but its selective use is recommended for patients with severe graft dysfunction showing severe hypoxemia and elevated pulmonary artery pressure [ 37 ]. Inhaled epoprostenol was recently reported to be equivalent to inhaled NO for preventing severe graft dysfunction [ 38 ]. However, it remains unclear whether either inhaled NO or epoprostenol conferred any benefit and whether their routine use to prevent graft dysfunction should be supported.…”
Section: Management Of Mechanical Ventilationmentioning
confidence: 99%
“…International registries have reported an incidence of PGD-3 at 72 hours approaching 15%, but it is unusual to observe rates exceeding 5% to 10% in experienced centers . The nonrandomized trial by Moreno et al, cited in the study by Ghadimi et al, did show a high incidence (45%) of PGD-3 at 72 hours, which was reduced to 17.2% with iNO . However, that report presented insufficient patient information, methods for patient selection or treatment allocation, and potentially has considerable selection bias.…”
mentioning
confidence: 96%
“…In the blinded randomized clinical trial by Ghadimi et al, inhaled epoprostenol was reported to be equivalent to inhaled nitric oxide (iNO) in preventing severe grade 3 primary graft dysfunction (PGD-3). While institution-specific contracts greatly influence the cost of iNO, it is generally an expensive therapy.…”
mentioning
confidence: 99%